Leprechaunism with mosaicism 46, XX/47, XX extra ring chromosome. Issue 5 (October 1977) - Ventruto, V; Sebastio, L; Sebastio, G; DeMasi, R V; Vota, U; Farina, L; Festa, B
Abstract : A case of leprechaunism with a chromosomal abnormality is reported. The patient was a female infant, born to healthy, consanguineous young parents. Her course was one of extreme marasmus, with death at 3 months of age. She presented the classical features of the syndrome and chromosome mosaicism 46, XX/47, XX, +r(?). It was not possible to identify the origin of the extra ring chromosome. It is difficult to establish the role of such a cytogenetic finding in the aetiology of the syndrome.